MANFAAT ELECTRONIC WORD OF MOUTH PADA KEPUTUSAN PEMBELIAN (STUDI KASUS: @AFTERGLOW.THELABEL) - Aurelia Indri Maria Rooselinda; Dewi Anggraini Harliwong (Universitas Tidar, 2022)
Electronic word of mouth (e-WOM) is a word of mouth marketing done with orally and in writing, distributed through electronic media, and containing consumer experiences when purchasing products. This study aims to look at the benefits of e-WOM on consumer purchasing decisions, especially the @afterglow.thelabel, the role of e-WOM in increasing sales of the @afterglow.thelabel, and the form of marketing communication strategies undertaken by @afterglow.thelabel to get a positive e-WOM. The method used in this research is descriptive qualitative with a constructive paradigm. The method of data collection was done by semi-structured interviews and using data triangulation for the validity of the data. It was found that e-WOM is useful and plays a role in consumer purchasing decisions @afterglow.thelabel.